Genome-Wide Detection of Runs of Homozygosity in Laiwu Pigs Revealed by Sequencing Data - Fang, Yifei; Hao, Xinyu; Xu, Zhong; Sun, Hao; Zhao, Qingbo; Cao, Rui; Zhang, Zhe; Ma, Peipei; Sun, Yanxiao; Qi, Zengmin; Wei, Qingkui; Wang, Qishan; et al. (Frontiers in Genetics, 2021)
Laiwu pigs, distinguished by their high intramuscular fat (IMF) of 7%~9%, is an indigenous pig breed of China, and recent studies also found that Laiwu pigs showed high resistance to Porcine circovirus type 2(PCV2). However, with the introduction of commercial varieties, the population of Laiwu pigs has declined, and some lineages have disappeared, which could result in inbreeding. Runs of homozygosity (ROH) can be used as a good measure of individual inbreeding status and is also normally used to detect selection signatures, so as to map the candidate genes associated with economically important traits. In this study, we used data from Genotyping by Genome Reducing and Sequencing (GGRS) to investigate the number, length, coverage, and distribution patterns of ROH in 93 Chinese Laiwu pigs and identified genomic regions with a high ROH frequency. The average inbreeding coefficient calculated by pedigree was 0.021, while that estimated by all detected ROH segments was 0.133. Covering 13.4% of the whole genome, a total of 7,508 ROH segments longer than 1 Mb were detected, whose average length was 3.76 Mb, and short segments (1–5 Mb) dominated. For individuals, the coverage was in the range between 0.56% and 36.86%. For chromosomes, SSC6 had the largest number (n=688), and the number of ROH in SSC12 was the lowest (n=215). Thirteen ROH islands were detected in our study, and 86 genes were found within those regions. Some of these genes were correlated with economically important traits, such as meat quality (ECI1, LRP12, NDUFA4L2, GIL1, and LYZ), immunity capacity (IL23A, STAT2, STAT6, TBK1, IFNG, and ITH2), production (DCSTAMP, RDH16, and GDF11), and reproduction (ODF1 and CDK2). A total of 6 significant GO terms and 9 significant KEGG pathways were identified, most of which were correlated with disease resistance and biosynthesis processes and one KEGG pathway was related to lipid metabolism. In addition, we aligned all of the ROH islands to the pig QTL database and finally found 8 QTLs related to the IMF trait. These results may help us understand the characteristics of Laiwu pigs and provide insight for future breeding strategies.